Complete chloroplast genome of an endangered endemic tree, handeliodendron bodinieri (levl.) rehder (sapindaceae) from karst forests of southwest China - Tian, Xinmin (Mitochondrial DNA B Resour, 2019)
Handeliodendron bodinieri (Sapindaceae) is an endangered monotypic species endemic to the karst forests in southwest China whose populations are now fragmented and the total number of individuals evidently decreased. In this research, we characterized the chloroplast (cp) genome of H. bodinieri using genome skimming. The whole cp genome was 155,291 bp long and comprised 137 genes, including 8 unique rRNAs, 40 tRNAs, and 89 protein-coding genes. The overall guanine-cytosine content of H. bodinieri cp genome was 37.8%. The phylogenetic analysis suggested that H. bodinieri is closely related to the genus Mangifera. This study will be useful for future studies on conservation genetics of this economically important endemic plant.